Middle Management’s Strategic Influence and Organizational Performance - Floyd, Steven W.; Wooldridge, Bill (Journal of Management Studies, 1997)
This study investigated relationships between middle managers’ formal position, their strategic influence and organizational performance. Among the 259 middle managers represented in the study, managers with formal positions in boundary–spanning sub–units reported higher levels of strategic influence activity than others. At the organizational level of analysis, the study found that firm performance was associated with more uniform levels of downward strategic influence, and more varied levels of upward influence among middle management cohorts. The findings suggest that middle managers’ strategic influence arises from their ability to mediate between internal and external selection environments. In addition, positive effects on organizational performance appear to depend on: (1) whether the overall pattern of upward influence is conducive to shifts in the network centrality of individual managers; and (2) whether the pattern of downward influence is consistent with an appropriate balance between the organization’s need for control and flexibility.